Best Murder of the Year - Bloch, Jon P. (St. Martin's Minotaur, 2002)
Gossip columnist Rick Domino is stunned when his lover, actor Shane Kirk, wins an Oscar for Best Actor but is nowhere to be found, and when Rick finally finds Shane, who is holding a gun and a dead body, Shane takes off, leaving Rick to face the police.
Keywords: Academy Awards (Motion pictures); Fiction; Fiction; Gay men; Fiction; Gossip columnists; Fiction; Hollywood (Los Angeles, Calif.); Fiction; Motion picture industry; dept.soc; faculty_collection

An Ethnographic Study of an American Conservative Synagogue - Laskin, Martin (Jewish studies (Lewiston, N.Y.) ; v. 24, 2002)
Keywords: Connecticut; Hamden; History; Liturgy; Jews; Sociological aspects; Conservative Judaism; Temple Beth Shalom (Hamden, Conn.); Synagogues; dept.soc; faculty_collection